Improving the dose distributions in minibeam radiation therapy: Helium ions vs protons. Issue 8 (25th June 2019) - Schneider, Tim; Patriarca, Annalisa; Prezado, Yolanda
Abstract : Purpose: Charged particle minibeam radiation therapy is a novel therapeutic strategy aiming at reducing the normal tissue complication probability by combining the normal tissue sparing of submillimetric, spatially fractionated beams with the improved dose deposition of ions. This may allow a safe dose escalation in the tumor and other targets. In particular, proton minibeam radiation therapy has already proven a remarkable increase of the therapeutic index for high‐grade gliomas in animal experiments. The reduced multiple Coulomb scattering and nuclear fragmentation of helium ions compared to protons and heavier ions, respectively, make them a good candidate for minibeam radiation therapy (MBRT). The purpose of the present work was to perform a comprehensive dosimetric comparison between proton and helium MBRT (pMBRT and HeMBRT). Methods: Proton and helium minibeams of the same range (7.7 cm) have been simulated in a water phantom and in CT images of an anonymized human head. The Monte Carlo simulation toolkit GATE v8.0 was used. Different beam sizes (1 and 3 mm) and multiple beam spacings were evaluated. Depth dose curves, lateral profiles, peak‐to‐valley dose ratios (PVDR), and dose‐averaged linear energy transfer (LET) were assessed. Furthermore, evaluations of the secondary products in the valley regions were carried out and a basic example of a treatment plan in pMBRT and HeMBRT was considered. Results: Compared to protons, helium ions yield a significantly improved Bragg‐peak‐to‐entrance dose ratio (BEDR) and higher PVDR at equal minibeam spacing. At the same time, due to the lower lateral scattering, dose homogenization in the target becomes more difficult for helium ions than for protons. To achieve a homogeneous target dose in HeMBRT, the minibeam spacing has to be reduced which in turn decreases the PVDR in normal tissues to values lower than those observed for protons. LET maps show up to 20%–30% higher values in the valley regions than in the peak regions for all evaluated cases. Helium ions lead to higher LET than protons at all depths, including the entrance region. However, this is compensated by a lower dose at shallow depths thanks to the improved BEDR of HeMBRT. Conclusions: Helium ions might offer a good choice for minibeam radiation therapy. They provide a more pronounced spatial fractionation than protons without the possible drawbacks linked to nuclear fragmentation of heavier ions. However, biological experiments are needed to evaluate whether the higher dose heterogeneity in the target volume in HeMBRT would still lead to an efficient tumor control, as in the case of pMBRT.